Frit skolevalg og lighed - Hansen, Claus (Politik, 2011)
The article discusses the normative implications of school choice in a Danish context. It focuses on two nor- mative principles – the principle of equality and the communitarian principle – and demonstrates how school choice can be criticized by appealing to both principles. More controversially, it argues that school choice cannot be justified with reference to parental rights. Parents do have the freedom to engage in activities with their children that jeopardize the principle of equality and the communitarian principle, but school choice is not one of them. Two Danish models of reducing the undesirable consequences of school choice are discussed: the Copenhagen Model and the Aarhus Model, respectively. The conclusion is that, given certain empirical assumptions, forcing school children to move to another school than the district school can be justified.